Microevolution rather than large genome divergence determines the effectiveness of legume-rhizobia symbiotic interaction under field conditions - Jozefkowicz, Cintia (2017)
Despite the vast screening for natural nitrogen-fixing isolates by public and privateconsortia, no significant progresses in the production of improved nitrogen-fixinginoculants for alfalfa production have been made in the last years. Here, we present acomprehensive characterization of the nitrogen-fixing strain Ensifer meliloti B399(originally named Rhizobium meliloti 102F34), probably the inoculant most widely usedin alfalfa production since the 1960s. Complete nucleotide sequence and genomeanalysis of strain B399 showed that the three replicons present in this commercialstrain and the model bacterium Ensifer meliloti 1021 are extremely similar to eachother in terms of nucleotide identity and synteny conservation. In contrast to thatobserved in B399-treated plants, inoculation of plants with strain 1021 did not improvenitrogen content in different alfalfa cultivars under field conditions, suggesting that asmall genomic divergence can drastically impact on the symbiotic phenotype.Therefore, in addition to the traditional screening of natural nitrogen-fixing isolates, thegenome engineering of model strains could be an attractive strategy to improvenitrogen fixation in legume crops.